Fluid Dynamic Characterization of a Polymeric Heart Valve Prototype (Poli-Valve) Tested under Continuous and Pulsatile Flow Conditions. Issue 11 (November 2015) - De Gaetano, Francesco; Serrani, Marta; Bagnoli, Paola; Brubert, Jacob; Stasiak, Joanna; Moggridge, Geoff D.; Costantino, Maria Laura
Purpose: Only mechanical and biological heart valve prostheses are currently commercially available. The former show longer durability but require anticoagulant therapy; the latter display better fluid dynamic behavior but do not have adequate durability. New Polymeric Heart Valves (PHVs) could potentially combine the hemodynamic properties of biological valves with the durability of mechanical valves. This work presents a hydrodynamic evaluation of 2 groups of newly developed supra-annular, trileaflet prosthetic heart valves made from styrenic block copolymers (SBC): Poli-Valves. Methods: 2 types of Poli-Valves made of SBC and differing in polystyrene fraction content were tested under continuous and pulsatile flow conditions as prescribed by ISO 5840 Standard. A pulse duplicator designed ad hoc allowed the valve prototypes to be tested at different flow rates and frequencies. Pressure and flow were recorded; pressure drops, effective orifice area (EOA), and regurgitant volume were computed to assess the behavior of the valve. Results: Both types of Poli-Valves met the minimum requirements in terms of regurgitation and EOA as specified by the ISO 5840 Standard. Results were compared with 5 mechanical heart valves (MHVs) and 5 tissue heart valves (THVs), currently available on the market. Conclusions: Based on these results, PHVs based on styrenic block copolymers, as are Poli-Valves, can be considered a promising alternative for heart valve replacement in the near future.